Foliage with pale yellow flowers - Gordon, John C. (photographer):::Creator::::::::::::
Photograph shows multiple types of foliage with small pale yellow or white flower spikes growing in a natural setting. In the foreground is a foliage that looks like ivy and possibly wild cucumber, man root or big root.